2009
DOI: 10.1242/jeb.027094
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal changes in thermoregulatory responses to hypoxia in the Eastern chipmunk (Tamias striatus)

Abstract: SUMMARYMammalian heterotherms are known to be more tolerant of low oxygen levels than homeotherms. However, heterotherms demonstrate extreme seasonality in daily heterothermy and torpor expression. Because hypoxia depresses body temperature (T b ) and metabolism in mammals, it was of interest to see if seasonal comparisons of normothermic animals of a species capable of hibernation produce changes in their responses to hypoxia that would reflect a seasonal change in hypoxia tolerance. The species studied, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…One consequence of a suppression of neuronal activity is that the hypoxic decline in T b produces a more variable thermoregulatory pattern due to the reduced gain or sensitivity of the CNS T b regulator. Precedence for this is observed in ectothermic studies showing a decreased precision of regulated T b in hypoxia (Cadena & Tattersall, 2009), as well as studies in mammals that demonstrate that the hypoxic decline in T b is more variable and also strongly dependent on ambient temperature (Barros et al 2001; Bishop et al 2001; Levesque & Tattersall, 2009). Indeed, one interesting result from the present study is the remarkable similarity between the changes in α and T th and those observed during different sleep states in rodents.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…One consequence of a suppression of neuronal activity is that the hypoxic decline in T b produces a more variable thermoregulatory pattern due to the reduced gain or sensitivity of the CNS T b regulator. Precedence for this is observed in ectothermic studies showing a decreased precision of regulated T b in hypoxia (Cadena & Tattersall, 2009), as well as studies in mammals that demonstrate that the hypoxic decline in T b is more variable and also strongly dependent on ambient temperature (Barros et al 2001; Bishop et al 2001; Levesque & Tattersall, 2009). Indeed, one interesting result from the present study is the remarkable similarity between the changes in α and T th and those observed during different sleep states in rodents.…”
Section: Discussionmentioning
confidence: 98%
“…Ground squirrels and other hibernating mammals have served as model animals for elucidating underlying thermoregulatory mechanisms common to mammalian T b control (Hammel et al 1973; Heller et al 1974; Florant & Heller, 1977; Larkin & Heller, 1996). Not only do they exhibit a profound reduction in T b and metabolism in hypoxia (Barros et al 2001) and a high degree of hypoxia tolerance (Drew et al 2007; Levesque & Tattersall, 2009), they also possess a very high α (Heller, 1978, 1979), a profound, cold‐activated thermogenesis from brown adipose tissue (Milner et al 1989), and have been shown to progressively lower T th as they enter into hibernation (Heller et al 1977). Thus, ground squirrels are a powerful model for exploring questions concerning the hypoxic response and thermoregulatory control.…”
Section: Introductionmentioning
confidence: 99%
“…This anapyrexic response widens the thermoneutral zone (TNZ) of an animal and induces a downward shift of its thermogenic threshold (Wood, ). Small rodents such as rats, mice, hamsters and chipmunks exhibit behavioural thermoregulation when exposed to acute hypoxia (Gordon & Fogelson, ; Levesque & Tattersall, ), as do a variety of other species, including goldfish, lizards and toads (Wood & Gonzales, ).…”
Section: Introductionmentioning
confidence: 99%
“… 7 Metabolic suppression is a physiological adaptation that is associated with oxygen consumption being actively reduced without causing any harm to the brain and other vital organs when exposed to hypoxic insults. 8 10 Metabolic suppression is the altered state of metabolism adaptation that occurs in hibernators 3 and hypoxia-tolerant species, 11 such as the naked mole-rat. 12 Since the metabolic rate is at a declined level in a hypoxia-tolerant mole-rat, the supply of adenosine triphosphate (ATP) through glycolysis and oxidative phosphorylation pathways must match the cellular demand for ATP.…”
Section: Physiological Mechanism Of Hypoxia Neuroprotection In the Namentioning
confidence: 99%